The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1002/adma.200304932
|View full text |Cite
|
Sign up to set email alerts
|

Polymer‐Mediated Alignment of Carbon Nanotubes under High Magnetic Fields

Abstract: Carbon nanotubes possess exceptional mechanical properties and superior thermal and electric properties.[1±4] Hence, nanotubes can be ideal reinforcement fibers for structural composites. For example, a cast composite film consisting of polystyrene and carbon nanotubes (5 % volume fraction) has increased the modulus by 100 % and the strength of the polystyrene by 25 %.[5] Moreover, the carbon nanotubes reinforcement increased the toughness of the composite by absorbing energy because of their high elastic beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
98
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(99 citation statements)
references
References 28 publications
0
98
0
1
Order By: Relevance
“…It is well known that WAXD is one of powerful tools for characterizing the degree of crystallite of CNTs aligned in polymer matrix [12][13][14]. Figure 3 shows the X-ray diffraction photographs taken from different X-ray incident directions for the rubber composite filled with 30 wt% CNTs aligned along the X-direction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that WAXD is one of powerful tools for characterizing the degree of crystallite of CNTs aligned in polymer matrix [12][13][14]. Figure 3 shows the X-ray diffraction photographs taken from different X-ray incident directions for the rubber composite filled with 30 wt% CNTs aligned along the X-direction.…”
Section: Resultsmentioning
confidence: 99%
“…Up to my knowledge, this is the first report on the production of the aligned carbon nanotube-filled rubber even though there were a few reports on the alignment of carbon nanotubes in polymer using the magnetic fields [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…For example, nickel wires and Fe 3 O 4 nanowires have been synthesized under the influence of magnetic fields [31 33], phase-selective synthesis of ferrosulfide microrods has been realized by a hydrothermal process using an amino acid additive under the influence of an external magnetic fi eld [34], Wang et al synthesized necklace-like noble metal hollow nanoparticle chains by using necklace-like Co nanoparticle chains, previously synthesized in a magnetic field-induced process, as a sacrificial template [35], and Gu et al demonstrated the alternating current magnetic fi eldinduced assembly of magnetite nanoparticles and its close relationship with the surface charge [36]. In addition, magnetic fields have also been used to direct the alignment of vanadium pentoxide ribbons [37], mouse osteoblast cells [38], carbon nanotubes [39], and polystyrene nanoparticles in an aluminum ferrite layered block [40]. Recently, our group has reported that Ni Co nanochains and magnetic flux-closure nanorings can be prepared directly in high yield in triethylene glycol solution containing polyvinylpyrrolidone (PVP) [41].…”
Section: Introductionmentioning
confidence: 99%
“…There exist several experimental works that display enhancement of mechanical properties of CNT-based composites by application of magnetic fields [5,6]. This fact is the chief motivation of this study.…”
Section: Introductionmentioning
confidence: 95%